2013
DOI: 10.5194/acp-13-2691-2013
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of the lifetimes of the major CFCs and CH<sub>3</sub>CCl<sub>3</sub> using atmospheric trends

Abstract: Abstract. Since the Montreal Protocol on Substances that Deplete the Ozone Layer and its amendments came into effect, growth rates of the major ozone depleting substances (ODS), particularly CFC-11, -12 and -113 and CH3CCl3, have declined markedly, paving the way for global stratospheric ozone recovery. Emissions have now fallen to relatively low levels, therefore the rate at which this recovery occurs will depend largely on the atmospheric lifetime of these compounds. The first ODS measurements began in the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
163
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(197 citation statements)
references
References 28 publications
14
163
4
Order By: Relevance
“…The model uses an annually repeating, monthly varying hydroxyl radical (OH) field from Spivakovsky et al (2000), which has been adjusted to match the observed trend in methyl chloroform (e.g. Rigby et al, 2013). For the gases in this paper, potential variations in OH concentration (e.g.…”
Section: Global Atmospheric Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The model uses an annually repeating, monthly varying hydroxyl radical (OH) field from Spivakovsky et al (2000), which has been adjusted to match the observed trend in methyl chloroform (e.g. Rigby et al, 2013). For the gases in this paper, potential variations in OH concentration (e.g.…”
Section: Global Atmospheric Modelmentioning
confidence: 99%
“…The firn air measurements were included in the inversion, with the age spectra from the firn model used to relate the firn measurements to high-latitude atmospheric mole fractions Vollmer et al, 2016). A 12-box model of atmospheric transport and chemistry was used to simulate baseline mole fractions, which assumed that the atmosphere was divided into four zonal bands (90-30 • N, 30-0 • N, 0-30 • S and 30-90 • S) and at 500 and 200 hPa vertically (Cunnold et al, 1994;Rigby et al, 2013). The model uses an annually repeating, monthly varying hydroxyl radical (OH) field from Spivakovsky et al (2000), which has been adjusted to match the observed trend in methyl chloroform (e.g.…”
Section: Global Atmospheric Modelmentioning
confidence: 99%
“…Boxes are also separated at altitudes represented by 500 and 200 hPa. Model transport parameters and stratospheric photolytic loss vary seasonally and repeat interannually (Rigby et al, 2013). For the CFCs analyzed here, loss in the atmosphere is dominated by photolytic destruction in the stratosphere.…”
Section: Agage 12-box Modelmentioning
confidence: 99%
“…Similar to the study by Vollmer et al (2016) for halons, the present analysis uses a firn air model to characterize the age of the CFCs in the firn air samples , the AGAGE 12-box model to relate atmospheric mole fractions to surface emissions (Rigby et al, 2013), two inversion approaches to estimate hemispheric emissions, and a Lagrangian transport model to study regional emissions of CFC-115 in northeastern Asia. …”
Section: Firn Model Global Transport Model and Inversionsmentioning
confidence: 99%
See 1 more Smart Citation